Controversies in the management of gastroschisis: a study of 40 patients. Issue 1 (January 1991) - Stringer, M D; Brereton, R J; Wright, V M
Abstract : Forty infants with gastroschisis were referred to two paediatric surgeons during a 13 year period. Overall survival was 90%. Nine patients were transferred in utero and 31 were referred postnatally. Birth weights, gestational ages, and Apgar scores were similar for both groups. Primary closure of the defect was successfully achieved in seven (78%) patients in the prenatally transferred group compared with 17 (55%) in the postnatal group. Significantly less postoperative assisted ventilation, and a trend in favour of early discharge home, were noted after prenatal transfer. Problems arising during postnatal transfer may have contributed to these differences. No major differences resulting from the mode of delivery were identified. Patients treated by primary closure fared significantly better than those undergoing staged repairs with prosthetic material. Prospective randomised studies are required to confirm these findings.